2014
DOI: 10.1111/bph.12668
|View full text |Cite
|
Sign up to set email alerts
|

Increased drug resistance is associated with reduced glucose levels and an enhanced glycolysis phenotype

Abstract: BACKGROUND AND PURPOSEThe testing of anticancer compounds in vitro is usually performed in hyperglycaemic cell cultures, although many tumours and their in vivo microenvironments are hypoglycaemic. Here, we have assessed, in cultures of tumour cells, the effects of reduced glucose levels on resistance to anticancer drugs and investigated the underlying cellular mechanisms. EXPERIMENTAL APPROACHPIK3CA mutant (AGS, HGC27), and wild-type (MKN45, NUGC4) gastric cancer cells were cultured in high-glucose (HG, 25 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 52 publications
4
57
0
Order By: Relevance
“…HeLa cell proliferation was arrested under HH. Similar results have been reported for breast MCF‐7 and several metastatic cells (human prostate DU 145 and gastric MKN45 and NUGC4) (Singh et al, ; Sedoris et al, ; Bhattacharya et al, ). It is known that low glucose (≤ 2.5 mM) arrests the cell cycle through a mechanism associated with down‐regulation of both cyclins and CDK4 in non‐cancer and cancer cells (Zang et al, ; Salpeter et al, ; Cheng et al, ; Roy and Banerjee, ).…”
Section: Discussionsupporting
confidence: 82%
“…HeLa cell proliferation was arrested under HH. Similar results have been reported for breast MCF‐7 and several metastatic cells (human prostate DU 145 and gastric MKN45 and NUGC4) (Singh et al, ; Sedoris et al, ; Bhattacharya et al, ). It is known that low glucose (≤ 2.5 mM) arrests the cell cycle through a mechanism associated with down‐regulation of both cyclins and CDK4 in non‐cancer and cancer cells (Zang et al, ; Salpeter et al, ; Cheng et al, ; Roy and Banerjee, ).…”
Section: Discussionsupporting
confidence: 82%
“…It is believed that autophagy can play both positive and negative roles in promoting apoptosis. Previous research demonstrated the cytoprotective role of autophagy in response to 5-FU treatment in gastric cancer cells (27,28), while a different study showed that 5-FU may suppress miR-30 to upregulate beclin-1 and thus induce autophagic cell death and cell proliferation arrest in gastric cancer cells (29). Nevertheless, many studies have shown that autophagy protects various tumor cells against apoptosis induced by chemotherapeutic drugs (23,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs can induce both apoptosis and autophagy in the treatment of cancer, and it was previously reported that autophagy helps cancer cells evade apoptosis, and thus contributes to chemoresistance (24). Additionally, cancer cells that respond to drugs by inducing autophagy are more drug-resistant (25): For example, in response to 5-fluorouracil (5-FU) and cisplatin, chemosensitive cell lines were found to undergo apoptosis, whereas chemoresistant populations underwent autophagy (25)(26)(27)(28). It is believed that autophagy can play both positive and negative roles in promoting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GLUT1 up‐regulation has been reported in numerous malignancies (Wang et al ., ). Increased GLUT1 is associated with the activation of mTOR leading to an increase in glycolysis and reduction in autophagy (Bhattacharya et al ., ; Buller et al ., ). Increased mTOR activation may also lead to increased GLUT1 expression, forming a positive feedback loop (Buller et al ., ).…”
Section: The Warburg Effect and Drug Resistancementioning
confidence: 98%